Enhancing Public Speaking Skills of Village Youth Through Service Learning and Participatory Action Research Models in Suko Village, Sidoarjo - Muhajir Sulthonul Aziz; Reiza Praselanova; Mohammad Rofiuddin; Novianto Puji Raharjo (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aimed to enhance the public speaking skills of rural youth through a service learning and participatory action research (PAR) approach. Conducted in Suko Village, East Java, the training involved 20 members of Karang Taruna “Laksa Muda.” The program focused on self-confidence, speech structure, and non-verbal communication. Using experiential learning methods, participants engaged in practice-based sessions, peer feedback, and reflective discussions. Theoretical frameworks included public speaking rhetoric (Ethos–Pathos–Logos), Kolb’s experiential learning cycle, and Freire’s empowerment pedagogy. Results indicated significant improvement in participants’ performance and engagement. The program fostered not only communication skills but also youth leadership and community participation. Supported by BPSDMP Kominfo Surabaya, the model shows strong potential for replication in other villages. This study affirms the role of higher education in empowering youth through context-sensitive training.